Behaviour of human dental pulp cells cultured in a collagen hydrogel scaffold cross‐linked with cinnamaldehyde. (6th January 2016) - Kwon, Y. S.; Lee, S. H.; Hwang, Y. C.; Rosa, V.; Lee, K. W.; Min, K. S.
Abstract: Aim: To investigate the effects of the cross‐linking agent cinnamaldehyde (CA) on differentiation of human dental pulp cells (hDPCs) cultured in a collagen hydrogel, which may be useful as a scaffold for regenerative endodontic therapy. Methodology: The odontogenic potential of hDPCs exposed to CA was examined using alkaline phosphatase (ALP) activity, Alizarin red S staining and real‐time polymerase chain reaction for odontogenic gene expression. The morphological features of hDPCs cultured in CA‐treated collagen were evaluated by scanning electron microscopy. Determination of cell numbers for evaluating proliferation was assessed by optical and fluorescence microscopy. To assess the mechanical properties of collagen treated with CA, setting time, compressive strength and surface roughness were measured. Statistical analysis was performed using Student's t ‐test compared with control ( P  =   0.05). Results: CA per se did not increase ALP activity, calcium nodule formation and expression of odontogenic‐related markers ( P  >   0.05). On the contrary, the proliferation and odontogenic differentiation of hDPCs cultured in a collagen scaffold was promoted in the presence of CA ( P  <   0.05). The setting time was significantly shortened, and the compressive strength and surface roughness were increased by treatment with CA ( P  <   0.05). Conclusions: Cross‐linking of collagen scaffolds by CA had beneficial effects with respect to attachment, proliferation and differentiation of hDPCs. Consequently, the application of cross‐linking agents such as CA may represent a new strategy for dentine–pulp complex regeneration.